Applications of Soil Moisture Sensor with Electrokinetic Ion Trap Mechanism - Ming-Hsi Lee; De-Jian Tsai; Chia-Yen Lee (International Journal of Distributed Sensor Networks)
A sensor comprising a pair of stainless steel planar electrodes and a capacitance meter is proposed for the real-time monitoring of the moisture content in soil. As rain falls on the ground, the moisture content of the soil between the two electrodes increases. The resulting change in the dielectric constant of the sensing material (soil) produces a corresponding change in the capacitance signal, from which the moisture content can then be inversely derived. The measurement performance of the proposed sensor is enhanced by means of an ion trap mechanism comprising two graphite mesh electrodes positioned orthogonally to the measurement electrodes. A DC voltage is applied to the two electrodes such that the anions and cations in the water are trapped by the positive and negative electrodes, respectively, thereby minimizing their effects on the sensing operation. The experimental results show that the proposed sensor achieves a high degree of sensitivity (i.e., 1.27  μ F/%) for gravimetric water contents ranging from 21 to 28%. Moreover, it is shown that the sensor has a repeatability of ±0.71% and ±0.55% for low and high gravimetric water contents, respectively.